Bangladesh National Muslim Information Centre (BNMIC): A Proposal - Md. Hanif Uddin; Md. Azharul Islam (Universiti Sains Islam Malaysia, 2024)
Bangladesh is 3rd largest Muslim country in the World after Indonesia and Pakistan. Muslim constitutes 87% of total population in Bangladesh. The Muslims of our country had glorious past and during medical period they ruled the country and contributed a lot in various fields especially in establishment of educational institutions popularly known as “Madrashas, production of literature in Persian and Urdu languages, development of architecture” and nourishment of secular values in the country. On the other hand, a large number of Muslims sacrificed themselves for the sake of freedom of the country in the year 1971. After independence, the country recorded a lot of progress in different fields. Unfortunately there was not established such type of Muslim Information centre for the development of the Muslim community. Though the government of Bangladesh tried to raise the status of Muslims through various welfare schemes but the Muslims did not adapt themselves with the government programs. It may be due to their ignorance, poverty, conservative out look and negative attitude. 2